Pertengkaran Terus Menerus Sebagai Alasan Paling Tinggi pada Perkara Cerai Gugat di Pengadilan Agama Kelas Ib Sungailiat - Wahyu Mahdi Prananta; Ifrohati (Journal of Sharia and Legal Science, 2024)
Divorce cases, which are one of the divorce cases that have increased in the period 2020-2022, were recorded at around 2,178 cases at the Sungailiat Class IB Religious Court. Therefore, the main problem in this study is what causes the increase in divorce cases and what the reasons are. The purpose of this study is to examine the reasons for divorce cases at the Sungailiat Class IB Religious Court according to Islamic law. This study is a type of field research, with a descriptive approach, the data in this study were obtained from primary data and secondary data, with data collection techniques used through interviews and documentation. The data was analyzed descriptively qualitatively. The results of the study stated that the increase in divorce cases at the Sungailiat Class IB Religious Court was caused by many factors. The highest reason for divorce cases was due to continuous quarrels and disputes. Reviewed from Islamic law regarding the reasons for divorce due to continuous quarrels and disputes decided by the Sungailiat Religious Court, it is based on the provisions and principles of Islamic law, this is because the divorce occurred after a peace effort was made by the Sungailiat Class IB Religious Court.